2013
DOI: 10.1073/pnas.1218821110
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution and unexpected variation among science faculty with education specialties (SFES) across the United States

Abstract: College and university science departments are increasingly taking an active role in improving science education. Perhaps as a result, a new type of specialized science faculty position within science departments is emerging—referred to here as science faculty with education specialties (SFES)—where individual scientists focus their professional efforts on strengthening undergraduate science education, improving kindergarten-through-12th grade science education, and conducting discipline-based education resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 4 publications
3
56
0
Order By: Relevance
“…Survey data revealed that faculty frequently mentioned they would select faculty with education research expertise as feedback providers and that education research expertise was a characteristic they sought when seeking out further feedback. Biologists have clearly come to value what SFES can offer to their departments (Bush et al ., 2013). For SFES, our findings about professional development suggest that efforts should focus more on instructional feedback and less on disseminating evidence-based teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…Survey data revealed that faculty frequently mentioned they would select faculty with education research expertise as feedback providers and that education research expertise was a characteristic they sought when seeking out further feedback. Biologists have clearly come to value what SFES can offer to their departments (Bush et al ., 2013). For SFES, our findings about professional development suggest that efforts should focus more on instructional feedback and less on disseminating evidence-based teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…Formerly studied under the frame of authentic research within the body of science education literature, more discipline-specific studies of CUREs and QCUREs, as different types of course-based research, became prevalent in the years 2013-2016. This may be due to the increasing number of scientists participating in science education research [74,75], and their ability to bring research into their own undergraduate classrooms. Indeed, such was the case with our study, where all four of the authors' astronomy expertise led to the development and/or dissemination of the projects in their own and others' classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying with and aligning with SoTL colleagues, even those investigating aspects of teaching and learning in the same discipline, may not be as easy as aligning with a more tightly focused disciplinary research community (Kelley, 2008). Bush, Pelaez, Rudd, Stevens, Tanner, and Williams (2013;2015) identified that in science at least, a significant proportion of academics who undertake SoTL feel there is often a misalignment between the expectations of their employers and their own goals for undertaking SoTL research. Additionally, their employers frequently "misunderstand the nature of scholarly activity" that is SoTL in the science classroom (Bauer, Clevenger, Cole, Jones, Kelter, Oliver-Hoyo, & Sawrey, 2008, p. 900).…”
Section: Introductionmentioning
confidence: 99%